DEVELOPING ACCOUNTANTS FOR ATOMIC ENERGY. - Slaton, William H. (The Accounting Review, 1955)
The article focuses on the requirement of accountants within the Atomic Energy Commission. The commission's Junior Management Development Program employs ten persons each year to help provide a flow of trained people. One of the qualifying fields is business administration. These people are needed because atomic energy just in the past few years has become big business, and one of the fastest growing industries in the United States. The training program is aimed at the graduates to be sound on technical points, such as inventory pricing, depreciation, testing of records for audit purposes, bank reconciliation, and all the others. The accountant, the auditor, the budget analyst, must not only have sound ideas and thoughts, but he must be able to present these thoughts so that they are understood, are convincing, and secure a desired response. The training and examination methodology of the program is discussed in the article. The author suggests a need for improvement in both written and oral presentations.